Formula: sqr((x2-x1)^2 + (y2-y1)^2)
sqr((-4-2)^2 + (-7+2)^2)
sqr(-6)^2 + (-5)^2)
sqr(36)+(25)) = sqr(61)
The answer is A. sqr(61)
Answer:
y = 5
Step-by-step explanation:
−x+y=0 −2x+y=−5
Multiply the first equation by -2
-2(-x+y=0)
2x-2y =0
Add this to the second equation
2x-2y =0
−2x+y=−5
-------------------
0x -y = -5
-y =-5
Multiply by -1
y = 5
Answer:
Is there a picture you can take
Step-by-step explanation:
The answer is 1.
8x6=48
8x5 + 8x1 = 48
i don’t know but you could prob use photo math. that would hell